Primary gynecologic melanoma: A report of two unusual cases - Jessica L. Berger; Daman Samrao; Marilyn Huang; Alexander B. Olawaiye (Gynecologic Oncology Reports, 2015)
Background: Primary ovarian and cervical melanomas are extremely rare tumors with a poor prognosis. Diagnosis requires a high index of suspicion as presentation can mimic benign conditions clinically and other neoplasms histologically. Cases: A 41 year-old with an adnexal mass underwent surgical staging for a stage IA ovarian melanoma. Imaging revealed a brain metastasis treated with radiation. Subsequent nodal recurrence was treated with immune and targeted therapies. She is alive with disease at 61 months follow-up. A 54 year-old presented after endocervical melanoma was diagnosed with polypectomy. She underwent radical hysterectomy, lymphadenectomy, and adjuvant brachytherapy. Immediate post-treatment imaging revealed widespread liver and pulmonary metastasis, currently being treated with ipilimumab. Conclusion: Immunohistochemistry can facilitate the diagnosis of gynecologic melanoma, and multidisciplinary treatment is recommended.